Book Review: Rethinking Islam Movement in Indonesia Post-authoritarianism - Christantyawati, Nevrettia (Faculty of Communications Science, Dr. Soetomo University, 2017)
Van Dijk, K., & Kaptein, N. J. (ed) (2016).Â Islam, Politics and Change: The Indonesian Experience after the Fall of Suharto. Leiden: Leiden University Press. 333 pages.